Bersama Masyarakat Membangun Lingkungan Yang Lebih Bersih, Hijau Dan Berkelanjutan - Agung Siswahyu; Ridwan Prasetyo; Muhammad Zaidan Fayyadh; Marcellino; Farrel Muhammad Dava; Muhammad Thoriq; Yossie Saputra; Frans Destri Bintang Shahry; Ifnu Nur Hidayat; Ega Jerilian (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
The Community Service Program (Kuliah Kerja Nyata or KKN) in Setia Mekar Village was carried out for one month, focusing on improving environmental quality, health, and community empowerment. Activities included communal work (gotong royong) and planting vegetation around the RW 005 Post to create a clean and green environment, dish soapmaking training for Posyandu (integrated health service post) mothers as a productive economic skill, personal hygiene education for PAUD (early childhood education) children through hands-on practice in proper tooth brushing and handwashing, as well as eco-print tote bag making training to introduce environmentally friendly creativity. In addition, the program involved painting the Posyandu building with the community to enhance the appearance of health facilities, and concluded with a closing event as a form of appreciation for the collaboration built. The results of the KKN showed an increase in community awareness of environmental cleanliness, the adoption of clean and healthy living behaviors, and the development of creative skills with potential as business opportunities. This program is expected to have a sustainable positive impact on the welfare of the Setia Mekar Village community.